Comparison of the Effect of Some Additives on Concrete – The Engineering and Planning Aspect (Journal of Basic and Applied Sciences, 2023)
Information and results from previous studies on different concrete additives were collected and compared in terms of their effects on concrete properties such as density and compressive strength. The aim of this research is to select the most appropriate additive regarding its effect on concrete resistance, light weight, material cost, and availability in areas near the work site.The study concluded that iron furnace slag is abundantly available, with quantities estimated at about 300 kg per ton of iron ore, making it a cheap and easily accessible material. Sawdust is also available and relatively low-cost compared to other materials, while palm fronds are abundant in Libya but expensive due to the difficulty of grinding them according to the required gradation.This subject has significant economic importance since it contributes to reusing waste materials in structural applications, especially with increasing population density and the challenges of waste disposal and its negative environmental impacts. Using furnace slag as a coarse aggregate alternative reduces environmental effects, while sawdust and palm fronds are considered environmentally friendly alternatives as they are natural materials and do not cause harmful residues when mixed with concrete.The results showed that increasing the percentages of these additives (furnace slag, sawdust, and palm fronds) generally led to lower compressive strength and reduced density of concrete, while providing new properties such as light weight
Keywords: Concrete; Concrete additives; Furnace slag; Sawdust; Palm fronds